FRI0038 Anti-Hinge Antibodies Recognize IGG Subclass- and Protease-Restricted Hinge neo-Epitopes. (15th July 2016) - Falkenburg, W.; van Schaardenburg, D.; Ooijevaar-de Heer, P.; Tsang-A-Sjoe, M.; Bultink, I.; Voskuyl, A.; Bentlage, A.; Vidarsson, G.; Wolbink, G.; Rispens, T.
Abstract : Background: Anti-hinge antibodies (AHAs), autoantibodies that target neo-epitopes exposed in the hinge of IgG molecules after cleavage by proteases, can be found in healthy individuals but more frequently and at higher levels in rheumatoid arthritis (RA) patients. Recently, our group reported that AHAs in RA patients specifically target pepsin-cleaved hinge of IgG4. Objectives: Determine the presence of AHAs and their specificity for protease- and IgG subclass-restricted neo-epitopes in healthy donors (HDs) and patients with RA or systemic lupus erythematosus (SLE). Methods: Presence of AHA-reactivity and specificity of AHAs for protease- and IgG subclass-restricted neo-epitopes was determined with newly developed enzyme-linked immunosorbent assays (ELISAs) that measure AHA-reactivity against the hinge of F(ab')2-fragments generated by cleaving the four IgG subclasses with pepsin or IdeS, an IgG-degrading enzyme of Streptococcus pyogenes (Figure 1 ). Inhibition experiments were performed to investigate cross-reactivity and results were confirmed using a novel Surface Plasmon Resonance imaging (SPRi) array. Results: Reactivity against at least one of eight F(ab')2-targets was found in 68% (51/75) of HDs, 65% (47/72) of SLE patients, and 83% (59/73) of RA patients. Individual AHA responses targeted protease-restricted neo-epitopes. Reactivity against IdeS-generated F(ab')2-targets was found more frequently in all three groups, but reactivity against pepsin-generated F(ab')2-targets better discriminated between RA patients and HDs or SLE patients, with significantly higher levels of AHAs against pepsin-cleaved IgG1 and IgG3 in RA compared to SLE and HDs respectively. The most discriminatory AHA-reactivity in RA was against pepsin-cleaved IgG4, with at least 5x more positive sera compared to HDs and SLE and significantly higher levels (P<0.0001). Cross-reactivity for different IgG subclasses was only observed for subclasses having homologous F(ab')2 C-termini (IgG1, IgG3, IgG4). Conclusions: Anti-hinge antibodies specifically recognize IgG subclass- and protease-restricted hinge neo-epitopes, possibly generated under (chronic) inflammatory conditions. The protease-restricted specificity of AHAs suggests that different AHA responses have developed under distinct inflammatory or infectious conditions and may be markers of -and participants in such conditions. In the proteolytic environment of the inflamed joint AHAs may contribute to immune complex formation, promoting further tissue destruction and inflammation. Disclosure of Interest: None declared